The Cathedral Chapter of Pamplona: Social Composition, Canonical Careers, and Conflictiveness in the Thirteenth Century (1194-1266) (Edad Media. Revista de Historia, 2018)
This research article compiles the results of a prosopographical study of the canons of the Cathedral of Pamplona during the first half of the thirteenth century, that has enabled us to determine the geographical and social origin of these clerics, to connect the community with the social framework of the city and the kingdom, and to revise the conflicts that broke out in the period within the institution, and in particular, between the canons and the bishops. Besides, the analysis has revealed the characteristics of the social promotion afforded by the charter. In conclusion, we can assert that this growing stage of the Church of Pamplona coexists with serious difficulties that prove how these years turned out to be a decisive period in the chapter’s development.
Keywords: Cathedral Chapters; Ecclesiastical Elites; Ecclesiastical Hierarchy; Ecclesiastical Conflictiveness; Pamplona; Reign of Navarre; Thirteenth Century